Comparison of risk of acute kidney injury between patients receiving the combination of teicoplanin and piperacillin/tazobactam versus vancomycin and piperacillin/tazobactam - Chi-Hao Shao; Chih-Hsun Tai; Fang-Ju Lin; Chien-Chih Wu; Jann-Tay Wang; Chi-Chuan Wang (Journal of the Formosan Medical Association, 2022)
Background/purpose: To compare the risk of acute kidney injury (AKI) among patients receiving teicoplanin (TA) plus piperacillin/tazobactam (TZP) versus vancomycin (VAN) plus TZP. Methods: This was a retrospective cohort study using electronic health records. Patients were included if a combination of glycopeptide and TZP or other selected β-lactams were used during hospitalization. In the main analysis, two study groups were identified: TA + TZP and VAN + TZP. We used 1:1 propensity score matching to control for potential confounders, and hazard ratio (HR) of AKI between study groups was calculated. We further compared the risk of AKI between patients receiving VAN + TZP and VAN + β-lactams as an auxiliary analysis to verify the validity of the study design. Results: The final sample contained 211 pairs of patients receiving either TA + TZP or VAN + TZP. The median dosage of TA and VAN were 10.3 and 26.7 mg/kg/day, respectively. The median trough level of VAN was 12.3 mg/L. The AKI risk in the TA + TZP group was similar to that in the VAN + TZP group (12.3% vs. 11.4%; HR = 1.25 [0.72–2.18], p = 0.44). The auxiliary analysis showed a higher risk of AKI in the VAN + TZP group than in the VAN + β-lactam group (13.2% vs. 9.6%; HR = 1.63 [1.04–2.55], p = 0.03). Conclusion: Our study results showed that the risk of AKI were similar for patients receiving TA + TZP and VAN + TZP. However, low VAN and high TA dose may play a role in this finding. Further investigation on the association between AKI and TA + TZP is required.